2012
DOI: 10.5051/jpis.2012.42.5.173
|View full text |Cite
|
Sign up to set email alerts
|

The thickness of alveolar bone at the maxillary canine and premolar teeth in normal occlusion

Abstract: PurposeThe main purpose of this study was to investigate bone thickness on the buccal and palatal aspects of the maxillary canine and premolars using cone-beam computed tomography (CBCT). The differences between left- and right-side measurements and between males and females were also analyzed.MethodsThe sample consisted of 20 subjects (9 males and 11 females; mean age, 21.9±3.0) selected from the normal occlusion sample data in the Department of Orthodontics, The Catholic University of Korea. The thickness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…Immediate implant placement enables one-stage surgery and eliminates bone recovery time. In this technique, dimensions of alveolar process which is selected for dental implant placement and relationships with adjacent anatomical structures of this region should be carefully assessed [8,35] . Jin et al [35] studied bone thickness evaluation on the buccal and palatal aspects of the maxillary canine and premolars using CBCT and it was concluded that CBCT images might be advantageous in preoperative planning of dental implants [35] .…”
Section: Regenerative Periodontal Therapy and Bone Graftsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate implant placement enables one-stage surgery and eliminates bone recovery time. In this technique, dimensions of alveolar process which is selected for dental implant placement and relationships with adjacent anatomical structures of this region should be carefully assessed [8,35] . Jin et al [35] studied bone thickness evaluation on the buccal and palatal aspects of the maxillary canine and premolars using CBCT and it was concluded that CBCT images might be advantageous in preoperative planning of dental implants [35] .…”
Section: Regenerative Periodontal Therapy and Bone Graftsmentioning
confidence: 99%
“…In this technique, dimensions of alveolar process which is selected for dental implant placement and relationships with adjacent anatomical structures of this region should be carefully assessed [8,35] . Jin et al [35] studied bone thickness evaluation on the buccal and palatal aspects of the maxillary canine and premolars using CBCT and it was concluded that CBCT images might be advantageous in preoperative planning of dental implants [35] . As a summary, in cases, where two-dimensional imaging is an inadequate method for accurate diagnosis of periodontal defect configuration and guiding for appropriate treatment planning, three-dimensional radiographic examinations may be required.…”
Section: Regenerative Periodontal Therapy and Bone Graftsmentioning
confidence: 99%
“…36,37 The mean width of the facial alveolar bone wall is increased toward posterior regions. 37,38 Contradictory findings have been reported relative to the relationship between the thickness of buccal gingiva and that of the underlying facial osseous plate. In maxillary anterior teeth, Cook et al 39 found a significant association between gingival biotype and labial plate thickness while only a moderate or no correlation was demonstrated in other studies.…”
Section: Thickness Of Buccal Bonementioning
confidence: 90%
“…The data of 20 subjects (9 males and 11 females; mean age, 21.9±3.0 years) with normal occlusion were obtained from the Department of Orthodontics, The Catholic University of Korea (Seoul, Korea). The 20 subjects and the inclusion criteria were consistent with that of our previous study (12). Briefly, the criteria were: i) Periodontally healthy dentition; ii) normal occlusion; and iii) no previous orthodontic treatment.…”
Section: Methodsmentioning
confidence: 97%